Deregulated telomere transcription causes replication-dependent telomere shortening and promotes cellular senescence - Maicher, André; Kastner, Lisa; Dees, Martina; Luke, Brian (Nucleic acids research, 2012)
Abstract. Telomeres are transcribed into non-coding TElomeric Repeat containing RNAs (TERRA). We have employed a transcriptionally inducible telomere to inves
Published online 2 May 2012
Gesehen am 08.08.2018